A Dramatic Response to Immune Checkpoint Inhibitor in A Patient with A Bulky Intra Cardiac Metastasis in Renal Cell Carcinoma: A Case Report - Florent, Peyraud; Marine, Gross-Goupil; Alain, Ravaud (Archives of Clinical and Medical Case Reports, 2019)
Background: Oral multitargeted tyrosine kinase inhibitors (TKIs) and immune checkpoint inhibitors (IO), have increased survival of patients with metastatic renal cell carcinoma (mRCC). Common sites of mRCC are lymph nodes, lung, liver and bone, but some unexpected clinical presentations sometime occurred as cardiac metastasis without validated treatment. We described a case report of a patient presenting cardiac metastasis treated with IO who showed a dramatic, durable response, which was prolonged despite stopping the drug. Case Presentation: A 51-year-old man was treated by radical nephrectomy and hepatic segmentectomy in 2008 for a locally advanced clear cell renal cell (CCRC) carcinoma. Between 2009 and 2015, successive localized progressions were treated by several focal treatments, including surgery and interventional radiology, and intermittent TKIs. Because of systemic dissemination with a bulky intracardiac metastasis, the patient received anti-PD1 nivolumab with a dramatic response. In 2017, a new disease progression at the site of the nephrectomy recurrence was treated with surgery. But, subsequent to the surgery, an acute promyelocytic leukemia was diagnosed. A specific treatment was started and nivolumab was not reintroduced. In March 2018, CR of the leukemia with negative MRD was achieved. In March 2019, the dramatic efficacy on the intra cardiac metastasis and nephrectomy lodge was still maintained. Conclusions: Cardiac metastases are considered to be rare and no standard treatment is validated. We report the first case of an IO blocker response on cardiac metastases in the context of mRCC. In addition, immunotherapy efficacy was maintained over time, even after treatment discontinuation and regardless of metastasis localization.